The longevity paradox : how to die young at a ripe old age - Gundry, Steven R; Lipper, Jodi (Harper Wave, an imprint of HarperCollinsPublishers, 2019)
From the moment we are born, our cells begin to age. But aging does not have to mean decline. World-renowned surgeon Dr. Steven Gundry has been treating mature patients for most of his career. He knows that everyone thinks they want to live forever, until they hit middle age and witness the suffering of their parents and even their peers. So how do we solve the paradox of wanting to live to a ripe old age<U+2014>but enjoy the benefits of youth? This groundbreaking book holds the answer. Working with thousands of patients, Dr. Gundry has discovered that the “diseases of aging” we most fear are not simply a function of age; rather, they are a byproduct of the way we have lived over the decades. In The Longevity Paradox, he maps out a new approach to aging well<U+2014>one that is based on supporting the health of the “oldest” parts of us: the microorganisms that live within our bodies. Our gut bugs<U+2014>the bacteria that make up the microbiome<U+2014>largely determine our health over the years. From diseases like cancer and Alzheimer<U+2019>s to common ailments like arthritis to our weight and the appearance of our skin, these bugs are in the driver<U+2019>s seat, controlling our quality of life as we age.